Website Dinas Sosial, Pemberdayaan Perempuan, dan Perlindungan Anak Provinsi Papua Tengah - Jhoni Ugi Mote; Ester Ayuk Pusvita (STMIK Pesat Nabire, 2026)
This article discusses the design and development of a website for the Central Papua Provincial Social Service, Women's Empowerment, and Child Protection. This website is designed as a means of complete, accurate, and easily accessible information to the public. The main goal of development is to increase transparency, accountability, and strengthen communication between the service and the community. The design process includes needs analysis, user-friendly interface design, and the development of responsive web technology-based systems. The main features implemented include the presentation of program and service information, news and activity publications, and interactive channels for complaints and consultations. The results of the development show that the website is able to facilitate public access to official information, improve the efficiency of data dissemination, and support openness in public services. Thus, this website is expected to be a strategic medium in strengthening the role of the Central Papua Provincial Social Service, Women's Empowerment, and Child Protection in providing transparent, accountable, and community-oriented services.